Revisiting the Dynamic MacroeconomicEffects of Real Exchange Rate and Economic growth: Application of Structural Vector Autoregressive (SVAR) Analysis - Yasmeen, Najma; Yasmin, Fouzia; Safdar, Noreen; Khatoon, Sabila (The journal of contemporary issues in business and government, 2021)
This research study endeavor to inspect the influence of real effective exchange rate on level of real GDP consumer price index (CPI) by using restricted VAR (VECM) econometrics approach for Pakistan economy over the period 1980-2020. We examined the bivariate relationship between real effective exchange rate and level of real GDP. It was concluded a negative correlation between these two variables. Thelong-term interrelationship among real effective exchange rate, CPI price level, and level of real GDP has also been examined by employing Johansen co-integration. By utilizing various VECM models we have found the long-term causality (A) from CPI price and level of output to the real effective exchange rate, and (B) from the real effective exchange rate, CPI price level `and level of real output to M2 money supply and (C) from the real effective exchange rate, M2 and real output level to CPI price level. The money supply (M2) growth has a very strong positive impact on both levels of real GDP and CPI level.